2011
DOI: 10.1143/jjap.50.09md03
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Induced by Various Input Beam Polarizations in All-Optical Magnetic Recording

Abstract: In this work, we investigate the role of the input optical beam polarization on the resulting magnetic field generated for applications like all-optical magnetic recording (AOMR). We consider two mechanisms by which a laser source gives rise to a magnetic field: the inverse Faraday effect and an additional mechanism, referred to as optically-induced spin-orbit coupling, which is especially relevant under the very large electrical field associated with ultrashort laser pulse excitation. We compare the direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The numerical model was defined, solved and analyzed using the commercial software COMSOL 4.1 Multiphysics. Since in AOMR the circularly polarized light is the most favorable polarization -it leads to three desirable features for the optically-induced magnetization: a relatively high spatial confinement, a direction nearly perpendicular to the opto-magnetic medium and a large magnitude [60,61] -, a single mode with circular polarization is launched into the microfiber tip conical cut structure shown in Fig. 3.…”
Section: Device Designmentioning
confidence: 99%
“…The numerical model was defined, solved and analyzed using the commercial software COMSOL 4.1 Multiphysics. Since in AOMR the circularly polarized light is the most favorable polarization -it leads to three desirable features for the optically-induced magnetization: a relatively high spatial confinement, a direction nearly perpendicular to the opto-magnetic medium and a large magnitude [60,61] -, a single mode with circular polarization is launched into the microfiber tip conical cut structure shown in Fig. 3.…”
Section: Device Designmentioning
confidence: 99%
“…Relativistic electron bunches [5] have proven effective but the need for electron accelerators has limited their use. Alternative techniques based on the inverse-Faraday effect and on the optically-induced spin-orbit coupling effect rely on pulses of light to generate ultrafast magnetic pulses [6][7][8]. They are limited to a few material systems and are not amenable to strong spatial confinement of the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that all-optical magnetic super-resolution can be achieved by using binary amplitude and phase filters [7]. Recently the structure of circularly polarized evanescent waves in the focal region of the solid immersion lens with a sub-wavelength structure located at its bottom surface is analyzed and its application in high density magneto-optical recording is proposed [8,9]. However, it is observed that use of those techniques can reduce the magnetic focal point, but it cannot increase the depth of focus (DOF) of the field simultaneously.…”
Section: Introductionmentioning
confidence: 99%